Colorimetric Detection of the Tuberculosis Complex Using Cycling Probe Technology and Hybridization in Microplates. (June 2000) - Warnon, S.; Zammatteo, N.; Alexandre, I.; Hans, C.; Remacle, J.
Cycling probe technology (CPT) is a simple signal amplification method for the detection of specific target DNA sequences. CPT uses a chimeric DNA-RNA-DNA probe that is cut by RNase H when bound to its complementary target sequence. In this study, a hybridization assay was developed to detect biotinylated CPT products that result from the amplification of a Mycobacterium tuberculosis complex sequence. The chimeric probe was specifically designed to avoid the formation of secondary structures. The chosen capture probe was perfectly complementary to and was the same size as OL2, one of the two CPT products. The assay was based on the observation that a long sequence, such as the initial probe, was destabilized when bound to a small capture probe as a result of steric hindrance. The capture probe preferentially bound OL2 rather than the long initial probe. We added a prehybridization step with a helper DNA to enhance this discrimination between the two sequences. Colorimetric detection was performed using a peroxidase-streptavidin conjugate. After optimization, the non-isotopic hybridization assay allowed the detection of around 10 amol of target DNA. Besides being faster and easier to perform, this detection method was compared to electrophoresis separation and gave similar results.